Economic valuation for an environmental improvement in Leon, Guanajuato - Hernández Avila, Alejandro; Valdivia Alcala, Ramón; Romo Lozano, José Luis; Hernández Ortiz, Juan; Cuevas Alvarado, Cristóbal Martín (Revista Mexicana de Ciencias Agrícolas, 2018)
The present work addressed the problem of environmental pollution that exists in the municipality of Leon, Guanajuato. The metropolitan area of Leon is located in the seventh place of environmental pollution nationwide. The municipality has a population of 1 436 733 inhabitants and concentrates 27.7% of the total vehicular park of the state of Guanajuato and there is also established the most important footwear industry in Mexico, which is reflected in an environmental deterioration. Environmental pollution in Leon is considerable, since 57.2% of the surveyed population states that air quality is bad. This situation is reflected in the environmental deterioration and health problems of the inhabitants of the city. The main objective of the research has been to estimate the willingness to pay by the population of the municipality of Leon, Guanajuato, for the creation of a green fund to help mitigate the environmental problems of the municipality. To estimate the DAP, the contingent valuation method was used, for which surveys were conducted to the inhabitants of the city of León, in this way the necessary information was collected in order to obtain the DAP of the inhabitants of the city. The average DAP per inhabitant estimated was 131.15 pesos, earning an annual income of around 60 408 083.45 pesos; that is, 4 174 712.06 dollars in the year of 2014, taking as reference a vehicular park of 460 603 units (UAIP, 2015) for the same year.